(untitled) (Journal of Applied Learning and Teaching, 2022)
Teachers’ teaching methods are important as they have been shown to determine the students’ mathematics performance at secondary schools. However, it is evident that a significant number of students cannot continue to Grade 11, and there is a simultaneous decline in student enrolment in science-related degrees at the university level in Papua New Guinea (PNG). That being the case, this study aims to examine teaching methods employed by teachers in the classroom that affect Grade 12 students’ mathematics results. A mixed method research (qualitative and quantitative) approach is applied in this study. The interview data for Grade 12 mathematics teachers were analysed through a thematic approach to capture rich information. Three different teaching methods (teacher-centered, student-centered, and a mix of both teacher-centered and student-centered approaches) are identified in this study. It is evident in this study that the student-centred method has a significant influence on Grade 12 students’ mathematics results. The study concludes that more attention should be given to student-centered and mixed approaches, in order to improve Grade 12 students’ mathematics results.